Digital electroencephalography and long-term video electroencephalography - Ayat Allah Farouk (SpringerOpen, 2012)
EEG is the name commonly used for electroencephalography. EEG is an important test for diagnosing epilepsy. Conventional EEG has relatively low sensitivity in epilepsy, ranging between 25-56%. The combination of wake and sleep records gives a yield of 80% in patients with clinically confirmed epilepsy. Video-EEG is most helpful in determining whether seizures with unusual features are actually epilepsy.